Gonadal sex and temperature independently influence germ cell differentiation and meiotic progression in Trachemys scripta - Talia Hatkevich; Boris M. Tezak; Rafael D. Acemel; Vicky Wai Yee Chung; Darío G. Lupiáñez; Blanche Capel (Proceedings of the National Academy of Sciences, 2025)
In species with genetic sex determination (GSD), the sex identity of the soma determines germ cell fate. For example, in mice, XY germ cells that enter an ovary differentiate as oogonia, whereas XX germ cells that enter a testis initiate differentiation as spermatogonia. However, numerous species lack a GSD system and instead display temperature-dependent sex determination (TSD). In the red-eared slider turtle, Trachemys scripta , a TSD model species with a warm female promoting temperature (FPT) and cool male promoting temperature (MPT) system, temperature directly affects germ cell number. In this study, we examined whether temperature directly affects other aspects of germ cell differentiation/sex identity. We uncoupled temperature and the sexual fate of the gonad by incubating eggs at MPT and treating with 17β-estradiol, a scheme that invariably produces ovaries. Through analysis of meiotic spreads, we showed that germ cells in FPT ovaries follow the typical pattern of initiating meiosis and progress through prophase I. However, in E2-induced ovaries that incubated at MPT, germ cells entered prophase I yet fail to exhibit synapsis. These results, combined with our single-cell transcriptome analysis, reveal a direct effect of temperature on germ cell sexual differentiation independent of its effect on the gonadal soma. These results imply that not all events of meiosis are under somatic control, at least not in this TSD species.